Quality of public services at the Ahusen Village Office, Sirimau District, Ambon City - Aminah Bahasoan; Ahmad Rosandi Sakir; Humairah Almahdali (Department of Government Science, 2024)
The purpose of this study is to identify in depth the root of the problems faced by the Ahusen Village Office in terms of the quality of service to the community in Sirimau District, Ambon City. This study uses a type of quantitative descriptive research. The location of the study is the Ahusen Village Office, Sirimau District, Ambon City, The sample from the study for employees was taken by purposive sampling, which was 5 people. As for the community respondents, they were taken incidentally, namely 25 people. Thus the total number of samples is as many as 30 people The data that has been successfully collected related to each of the indicators mentioned above, will be analyzed by a quantitative descriptive method where the data obtained will be displayed through a frequency table, then to draw conclusions about each indicator seen through the tendency of respondents' answers. The results of the study showed that there was a variation in the perception of service quality at the Ahusen Village Office. While there are positive perceptions regarding employee appearance, computer availability, and employee willingness to hear complaints and provide assistance, there are significant challenges related to timeliness, accuracy, readiness, willingness, accuracy, knowledge, trust, and service security. Further evaluation and comprehensive corrective actions are needed to improve the quality of services and overall community satisfaction. These improvement efforts can include employee training, improved physical facilities, improved communication between employees and the community, and stricter supervision of the quality of services provided.